2015
DOI: 10.1370/afm.1843
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Correlates, and Outcomes of Multimorbidity Among Patients Attending Primary Care in Odisha, India

Abstract: PURPOSE Little information is available on multimorbidity in primary care in India. Because primary care is the first contact of health care for most of the population and important for coordinating chronic care, we wanted to examine the prevalence and correlates of multimorbidity in India and its association with health care utilization.METHODS Using a structured multimorbidity assessment protocol, we conducted a cross-sectional study, collecting information on 22 self-reported chronic conditions in a represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
110
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 18 publications
8
110
3
5
Order By: Relevance
“…The use of secondary services, measured as utilizing hospitalisations, had a prevalence twice as high among individuals classi ed as having multimorbidity and had a different pattern with regard to sex. In general, our results are in line with the ndings of other studies, which point to a twice as high probability of hospitalisations among individuals with multimorbidity [13,[31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…The use of secondary services, measured as utilizing hospitalisations, had a prevalence twice as high among individuals classi ed as having multimorbidity and had a different pattern with regard to sex. In general, our results are in line with the ndings of other studies, which point to a twice as high probability of hospitalisations among individuals with multimorbidity [13,[31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…The other nding of our study that diabetes patients above poverty line had a higher prevalence of comorbid conditions in comparison to diabetes patients from below poverty line is divergent from study ndings from developed countries but similar to ndings from studies conducted in India. [17,18] Wang et al in their study have also concluded that the number of visits to health facilities increased with increase in number of complications associated with diabetes. [3] Likewise, Grunier et al concluded that rise in the number of comorbid conditions raised the healthcare utilisation among diabetes patients.…”
Section: Discussionmentioning
confidence: 93%
“…The other finding is the higher prevalence of diabetes comorbidities among the above poverty line participants, which is contrary to finding from studies in developed countries but similar to findings of studies conducted in India. [17,18] Wang et al found a linear increase in outpatient hospital visits for each successive diabetic complication. [3] Similarly, Gruneir et al inferred that there is increased utilization of all health services with an increase in the number of comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%